(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Mastering specialised vocabulary is a central hurdle for learners in English-medium tourism programmes. Synthesising empirical studies published between 2015 and 2025, this review investigates how information technologies enhance the teaching and learning of tourism terminology. It maps the digital tools most frequently researched – mobile apps, augmented and virtual reality environments, multimodal corpora, and adaptive learning platforms – and analyses their pedagogical affordances for noticing, retention, and communicative transfer. A thematic comparison across 36 studies reveals three dominant implementation models: blended classroom integration, fully online self-access modules, and immersive task-based simulations. Outcome measures consistently show medium-to-large vocabulary gains, with virtual reality producing the highest effect sizes owing to contextual authenticity. Nonetheless, evidence for long-term retention and productive use remains limited. The review concludes by outlining research gaps – particularly in longitudinal designs and teacher professional development – and proposes an agenda for leveraging data analytics to personalise tourism vocabulary instruction in varied contexts across formal and informal settings.